ASSESSING BIODIVERSITY AND TOURISM POTENTIAL IN SAMPUNONG BOLO WILDLIFE SANCTUARY, PHILIPPINES: STRATEGIES FOR REHABILITATION AND SUSTAINABLE DEVELOPMENT - Jimmy de Julian (Indonesian Journal of Forestry Research, 2026)
This mixed methods research study investigates the biodiversity and tourism potential of Sampunong Bolo Wildlife Sanctuary in the Municipality of Sara, Province of Iloilo, Philippines, aiming to identify floral and faunal species, assess their tourism appeal, and propose strategies for rehabilitation and sustainable development. Primary data were collected through interviews and focus-group discussions with 14 purposively selected barangay residents and officials, complemented by secondary data from the Department of Environment and Natural Resources-Community Environment and Natural Resources Office (DENR-CENRO) of Sara. Thematic analysis was employed to analyze the interview data, identifying patterns and themes relevant to the sanctuary's current state and its potential for revival. The DENR CENRO data revealed 39 faunal and 100 floral species, highlighting the sanctuary's rich biodiversity. Moreover, the findings suggest significant tourism potential, with opportunities for wildlife observation, recreational activities, and cultural and economic activities. To rehabilitate the sanctuary, recommendations include implementing protective policies, enhancing infrastructure, installing informative signage, and employing environmental conservation efforts. These measures are expected to preserve biodiversity, improve visitor infrastructure, and promote sustainable tourism practices. Future research should focus on long-term ecological monitoring and assessing the socio-economic impacts of tourism development on local communities.